Australian Indigenous house crowding - Memmott, P.; Birdsall-Jones, Christina; Greenop, K. (AHURI Ltd, 2012)
This research project developed a model of Australian Aboriginal house crowding in order to provide policy-makers with ways to predict, measure and manage Aboriginal household overcrowding.